Analisis Kesesuaian Wisata Pantai dan Valuasi Ekonomi Pantai Tlangoh Kabupaten Bangkalan - Adam Prayoga Dwi Marara; Firman Farid Muhsoni (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2024)
ABSTRAKObjek wisata adalah salah satu tempat yang menjadi daya tarik bagi semua orang untuk berlibur. Analisa valuasi ekonomi berguna untuk menilai barang dan jasa lingkungan berupa keindahan alam yang dimanfaatkan sebagai objek wisata. Pantai Tlangoh merupakan pantai yang berpotensi menjadi salah satu destinasi wisata pantai. Penelitian ini bertujuan untuk mengetahui tingkat kesesuaian wisata dan valuasi ekonomi di Pantai Tlangoh. Hasil kesesuaian wisata Pantai Tlangoh memiliki nilai sebesar 95,5% dan dapat disimpulkan bahwa Pantai Tlangoh memiliki tingkat kesesuaian yang sangat sesuai. Nilai valuasi di Pantai Tlangoh sebesar Rp6.455.920.000 untuk nilai manfaat langsung, Rp645.592.000 untuk manfaat pewaris dan Rp300.000.000 untuk nilai keberadaan. Secara total nilai valuasi Pantai Tlangoh yaitu sebesar Rp7.401.512.000Kata kunci: valuasi ekonomi, kesesuaian wisata, Pantai TlangohABSTRACTA tourist attraction is a place that attracts everyone for a vacation. Ekonomic valuation analysis is usesful for assessing environmental goods and services in the form of natural beauty that are used as tourist attractions. Tlangoh beach is a beach that has the potential to become a beach tourism destination. This research aims to determine the level of suitability of tourism and economic valuation at Tlangoh Beach. The suitability results fot Tlangoh Beach tourism have a value of 95.5% and it can The valuation value at Tlangoh Beach is IDR 6,455,920,000 for the value of direct benefits, IDR 645,592,000 for the benefits of the heir and IDR 300,000,000 for the existence value. In total, the valuation value of Tlangoh Beach is IDR 7,401,512,000. be concluded that Tlangoh Beach has a very suitability. The valuation value at Tlangoh Beach is IDR 6,455,920,000 for the value of direct benefits, IDR 645,592,000 for the benefits of the heir and IDR 300,000,000 for the existence value. In total, the valuation value of Tlangoh Beach is IDR 7,401,512,000.Keywords: economic valuation, tourism suitability, Tlangoh Beach